Efektifitas Media Film dan Strategi Pembelajaran Semantic Mapping dalam Meningkatkan Penguasaan Kosakata Bahasa Inggris - Astuti, Natalia Tri; Hapsari, Fitri Senny (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the extent to which film media and semantic mapping learning strategies can improve student English vocabulary. This study uses a qualitative approach with individual action research methods which begins with surveys, observations, interviews and tests in the class. The research was carried out on the first semester students majoring in informatics using qualitative research methods. The results of the study, obtained by the results of film media and semantic mapping strategies, had a positive and significant effect on the improvement of students' English vocabulary. Conclusions, use of western films and effective semantic maping learning strategies to improve English vocabulary. Keywords: film media, semantic mapping, vocabulary, english